The Polarization-Index: A Simple Calculation to Distinguish Polarized From Non-polarized Training Intensity Distributions - Treff, Gunnar; Winkert, Kay; Sareban, Mahdi; Steinacker, Jürgen M.; Sperlich, Billy (Frontiers in Physiology, 2019)
The training intensity distribution (TID) of endurance athletes has retrieved substantial scientific interest since it reflects a vital component of training prescription: i) the intensity of exercise and its distribution over time are essential components for adaptation to endurance training and ii) the training volume (at least for most endurance disciplines) is already near or at maximum, so optimization of training procedures including TID have become paramount for success. This paper aims to elaborate the so-called polarization-index (PI) which is calculated as log10(Zone 1/Zone 2*Zone 3*100), where Zones refer to aggregated time or volume spent with low, mid or high intensity training. PI allows to distinguish between non-polarized and polarized TID using a cut-off > 2.00 a.U. and to quantify the level of polarization. Within this hypothesis paper, examples from the literature illustrating the usefulness of PI-calculation are discussed as well as its limitations. Further it is elucidated how the PI may contribute to a more precise definition of TID descriptors.